2019
DOI: 10.3390/polym11050846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly(styrene-ran-methyl acrylate) Inclusion on the Compatibility of Polylactide/Polystyrene-b-Polybutadiene-b-Polystyrene Blends Characterized by Morphological, Thermal, Rheological, and Mechanical Measurements

Abstract: A poly(styrene-ran-methyl acrylate) (S-MA) (75/25 mol/mol), synthesized by surfactant-free emulsion copolymerization, was used as a compatibilizer for polystyrene-b-polybutadiene-b-polystyrene (SBS)-toughened polylactide (PLA) blends. Upon compatibilization, the blends exhibited a refined dispersed-phase morphology, a decreased crystallinity with an increase in their amorphous interphase, improved thermal stability possibly from the thicker, stronger interfaces insusceptible to thermal energy, a convergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…According to the study of Eguiburu et al, 13 the PLA and PMA was apparently a miscible blend. Our latest research improved the PLA–SBS interfacial compatibility through the introduction of the poly(styrene‐ran‐methylacrylate) (S‐MA) compatibilizer (0, 0.5, 1, and 3 wt%) and found that 3 wt% S–MA is the most effective compatibilizer, as it has the most significant influence on the non‐isothermal crystallization behavior of the PLA/SBS (95/5 and 90/10 wt/wt) blends 24 …”
Section: Introductionmentioning
confidence: 99%
“…According to the study of Eguiburu et al, 13 the PLA and PMA was apparently a miscible blend. Our latest research improved the PLA–SBS interfacial compatibility through the introduction of the poly(styrene‐ran‐methylacrylate) (S‐MA) compatibilizer (0, 0.5, 1, and 3 wt%) and found that 3 wt% S–MA is the most effective compatibilizer, as it has the most significant influence on the non‐isothermal crystallization behavior of the PLA/SBS (95/5 and 90/10 wt/wt) blends 24 …”
Section: Introductionmentioning
confidence: 99%